1963
DOI: 10.1037/h0083281
|View full text |Cite
|
Sign up to set email alerts
|

Development of sexual behaviour in the male hamster.

Abstract: FUNCTIONALLY ADEQUATE SEXUAL BEHAVIOUR in mammals does not occur immediately after birth but instead appears after a sizable fraction of the individual's life has elapsed. The onset of mating behaviour is approximately coincident with widespread physiological changes in the organism. These facts are well established and need no further demonstration. However, a number of experiments have suggested that such details of sexual development as the age at onset of different responses and quantitative characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…These results resemble previous descriptions of male hamsters both in absolute levels and in the changes in III, EL, and IF exhibited across copulatory series (Arteaga-Silva et al, 2005; Beach & Rabedeau, 1959; Bunnell et al, 1977; Dewsbury, Lanier, & Oglesby, 1979; Huck, Lisk, Allison, & Van Dongen, 1986; Lehman, Powers, & Winans, 1983; Miernicki, Pospichal, & Powers, 1990; Rabedeau, 1963). They extend previous descriptions by documenting changes over series in MF and IR, but disagree with some previous reports of progressive increases in PEI (Beach & Rabedeau, 1959; Bunnell et al, 1977).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These results resemble previous descriptions of male hamsters both in absolute levels and in the changes in III, EL, and IF exhibited across copulatory series (Arteaga-Silva et al, 2005; Beach & Rabedeau, 1959; Bunnell et al, 1977; Dewsbury, Lanier, & Oglesby, 1979; Huck, Lisk, Allison, & Van Dongen, 1986; Lehman, Powers, & Winans, 1983; Miernicki, Pospichal, & Powers, 1990; Rabedeau, 1963). They extend previous descriptions by documenting changes over series in MF and IR, but disagree with some previous reports of progressive increases in PEI (Beach & Rabedeau, 1959; Bunnell et al, 1977).…”
Section: Resultssupporting
confidence: 90%
“…Because we did not view encounters from below, we cannot confirm that penile insertion accompanied all of these intromissions. Instead, our definition of this behavior incorporates both the pseudo- and complete-intromissions of Rabedeau (1963), who suggested that these are equivalent in their impact on the male. It also is the case that we relied entirely on overt behaviors and did not confirm the exchange of sperm during ejaculations.…”
Section: Methodsmentioning
confidence: 99%